Predictors of Source Memory Success and Failure in Older Adults - Cansino, Selene; Torres-Trejo, Frine; Estrada-Manilla, Cinthya; Ramírez-Barajas, Liuba; Pérez-Loyda, Miguel; Nava-Chaparro, Aidé; Hernández-Ladrón-deGuevara, Mariana; Ruiz-Velasco, Silvia (Frontiers in Aging Neuroscience, 2019)
Source memory decline has been identified as one of the types of memory most seriously affected during old age. It refers to our capacity to recollect the contextual information in which our experiences take place. Although most elderly adults will be affected by a progressive source memory decline, a subset of individuals will not follow this average pattern, and instead, their source memory capabilities will be preserved at a high level of functionality. Likewise, a minority of individuals will manifest an extreme decay of their source memory abilities. The objective of the present study was to identify among 120 potential predictors those that significantly contributed to these two extreme source memory outcomes. Spatial source memory was measured in a sample of 519 healthy individuals between 61 and 80 years old. Individuals who performed below the 20th and above the 80th percentiles in the source memory task were defined as individuals whose episodic memory failed and succeeded, respectively. Logistic models identified five and six significant predictors of source memory success and failure in old age, respectively. High source memory performance was mainly predicted by healthy cardiovascular markers and psychological traits, whereas low source memory performance was primarily predicted by consumption habits and by less engagement in mental activities. The models identified relevant biological and life experiences that underlie these unusual source memory outcomes in old age.